Peran Wanita dalam Pemberdayaan Ekonomi Kecil: Mikro Kredit di Kelurahan Petojo Utara - Holly Deviarti (Binus Business Review, 2010)
Women have a responsibility to meet the basic needs of families, when the husband has not been successful in adequately meeting family needs. Micro credit is taken from the method of Amanah Ikhtiar Malaysia (AIM), and applied in Petojo area, Central Jakarta. AIM Registration need women as participants in the micro-credit. This process begins with data collection on testing the ability of debtors, make arrangements for borrowers to work properly and return the loan. Implementation took place in a period of 1 year and micro- credit borrowers are selected from low economy class community. Before granting loans, microcredit and financial records training implementing agencies provide religious discourse about trade. The meeting between executives and micro-credit borrowers are held every week, the show began with a reading of the pledge, read the Koran and religious lectures. The desired results of this activity is full loan repayments, improved morale, improved family economy, but the reality is not as expected, honesty issues, decreased productivity and have became a boomerang for micro credit in Petojo area. Criteria for successful micro-credit application is simple, namely the intention to repay debt with honesty, and good effort in improving the quality of life.